Pemanfaatan Medan Elektromagnetik dalam Teknologi Pengobatan Modern - Novaldi Ramdani Reza; Rovino Alghafari; Errisa Zulqa Deswana; Muhammad Rifqi; Diyajeng Luluk Karlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The utilization of electromagnetic fields (EMF) in modern medical technology has become a significant focus of research. This study aims to explore the therapeutic effects of EMF, especially at low frequencies (ELF) and Pulsed Electromagnetic Fields (PEMF), in enhancing the healing of various medical conditions. The method used is a literature study by analyzing various sources from Google Scholar, Science Direct, and PubMed. The results showed that EMF therapy is effective in relieving pain, accelerating tissue healing, and improving the quality of life of patients with musculoskeletal disorders and fractures. Despite the many benefits, it is important to consider the potential health risks of long-term exposure to EMF. This study recommends the development of strict regulations and training for medical personnel to ensure the safe and effective use of EMF.